MUC1‐C drives myeloid leukaemogenesis and resistance to treatment by a survivin‐mediated mechanism. Issue 8 (15th May 2018) - Stroopinsky, Dina; Rajabi, Hasan; Nahas, Myrna; Rosenblatt, Jacalyn; Rahimian, Maryam; Pyzer, Athalia; Tagde, Ashujit; Kharbanda, Akriti; Jain, Salvia; Kufe, Turner; Leaf, Rebecca K.; Anastasiadou, Eleni; et al.
Abstract: Acute myeloid leukaemia (AML) is an aggressive haematological malignancy with an unmet need for improved therapies. Responses to standard cytotoxic therapy in AML are often transient because of the emergence of chemotherapy‐resistant disease. The MUC1‐C oncoprotein governs critical pathways of tumorigenesis, including self‐renewal and survival, and is aberrantly expressed in AML blasts and leukaemia stem cells (LSCs). However, a role for MUC1‐C in linking leukaemogenesis and resistance to treatment has not been described. In this study, we demonstrate that MUC1‐C overexpression is associated with increased leukaemia initiating capacity in an NSG mouse model. In concert with those results, MUC1‐C silencing in multiple AML cell lines significantly reduced the establishment of AML in vivo. In addition, targeting MUC1‐C with silencing or pharmacologic inhibition with GO‐203 led to a decrease in active β‐catenin levels and, in‐turn, down‐regulation of survivin, a critical mediator of leukaemia cell survival. Targeting MUC1‐C was also associated with increased sensitivity of AML cells to Cytarabine (Ara‐C) treatment by a survivin‐dependent mechanism. Notably, low MUC1 and survivin gene expression were associated with better clinical outcomes in patients with AML. These findings emphasize the importance of MUC1‐C to myeloid leukaemogenesis and resistance to treatment by driving survivin expression. Our findings also highlight the potential translational relevance of combining GO‐203 with Ara‐C for the treatment of patients with AML.